2015
DOI: 10.1659/mrd-journal-d-14-00107.1
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Encourage Intrafamily Farm Succession in Mountain Areas?

Abstract: Family farming plays a vital role in mountain areas. Its survival is related to multiple factors, including intrafamily farm succession. This study examined data on apple-producing family farms in an Italian Alpine valley, trying to identify which factors foster or discourage intrafamily succession and to what extent they do this, both at the farm level and from the potential successor's viewpoint. To do so, various farm, farmer, and individual characteristics were analyzed using probabilistic regression. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
5
29
1
8
Order By: Relevance
“…Além disso, Matte e Machado (2016), em pesquisa na região Sul do Brasil, consideram este um aspecto importante para permanência do jovem no campo e sucessão familiar. À medida que participam nas atividades da propriedade, aliado a um nível maior de estudo na área agrícola, os jovens e as jovens são influenciados a valorizar o trabalho na agricultura e permanecer no campo (Cavicchioli et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Além disso, Matte e Machado (2016), em pesquisa na região Sul do Brasil, consideram este um aspecto importante para permanência do jovem no campo e sucessão familiar. À medida que participam nas atividades da propriedade, aliado a um nível maior de estudo na área agrícola, os jovens e as jovens são influenciados a valorizar o trabalho na agricultura e permanecer no campo (Cavicchioli et al, 2015).…”
Section: Discussionunclassified
“…Corroborando com os dados da presente pesquisa, em estudo realizado na região central do RS, Prediger (2009) concluiu que, em contraste com a geração dos pais, em que predominavam famílias numerosas, os jovens e as jovens da atualidade compõem grupos familiares cada vez menores. Na Itália a probabilidade de um jovem assumir a propriedade familiar aumenta (15.5 %) à medida que diminui o número de jovens presentes na propriedade (Cavicchioli et al, 2015;Simeone, 2007). Já no Brasil, famílias pequenas conseguirão melhorar sua renda com a mecanização na agricultura (Alves, Lopes, & Contini, 1999).…”
Section: Discussionunclassified
“…Indeed, variables related to family succession can be quite complex. For example, the steady supply of family labor, typical of dairying (Mishra and El-Osta, 2007), may favor family ties and identity to dairy activity, thus influencing individual conditions to family succession; farming experience may influence family succession (Cavicchioli et al, 2015), which may help us to understand why farmers in Group 1 are more prone to family succession. Even in the economic perspective, the issue may be twofold: many dairy farmers, for example, consider the monthly income as a relevant element for family succession (Mishra and El-Osta, 2007), even if the profitability is not so interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to create a positive attitude among the youths towards agricultural occupations. One study showed that succession is +27% more likely when the children have specialized education in agriculture [20]. Therefore, related agencies can establish programs on agriculture or interlace relevant lessons into the different training courses or curriculum for the targeted groups of youths and children.…”
Section: Discussionmentioning
confidence: 99%